2nd National Plan of Action for Nutrition, Bangladesh (NPAN2) (2016-2025). - Islam Bulbul, Md M. (Tufts University. Tisch Library., 2020)
This presentation describes the background, purpose, and contentes of the 2nd National Plan of Action for Nutrition, Bangladesh (NPAN2); Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy